Cellular targets of mefloquine. (December 2021) - Ghosh, Debasish Kumar; Kumar, Abhishek; Ranjan, Akash
Highlights: Despite the chemoprophylactic potential of mefloquine, the toxic effects of mefloquine pose a challenge to the intensive use of this drug. Several mechanisms of mefloquine toxicity have been deciphered in vitro, and their characteristics remain to be correlated in clinical studies. It is important to understand how mefloquine toxicity overwhelms the druggability of the molecule in different tissues of the human body. Chemical modification of mefloquine is a viable option to reduce its toxicity and further use of modified mefloquine in non-malarial diseases. Abstract: Mefloquine is a quinoline-based compound widely used as an antimalarial drug, particularly in chemoprophylaxis. Although decades of research have identified various aspects of mefloquine's anti-Plasmodium properties, toxic effects offset its robust use in humans. Mefloquine exerts harmful effects in several types of human cells by targeting many of the cellular lipids, proteins, and complexes, thereby blocking a number of downstream signaling cascades. In general, mefloquine modulates several cellular phenomena, such as alteration of membrane potential, induction of oxidative stress, imbalance of ion homeostasis, disruption of metabolism, failure of organelle function, etc., leading to cell cycle arrest and programmed cell death. This review aims to summarize the information on functional and mechanistic findings related to the cytotoxic effects of mefloquine.